Indigenous Entrepreneurship that Creates a Sense of Place in the Traditional Shopping Areas - Kusumowidagdo, Astrid; Rembulan, Cicilia Larasati; Rahadiyanti , Melania; Wardhani, Dyah Kusuma (Bina Nusantara University, 2023)
The research aimed to investigate the tourism villages provided by indigenous people in Indonesia to create a sense of place for visitors. Indigenous communities in Indonesia were often faced with discrimination and negative stigma. However, by utilizing the potential of their cultural heritage and local resources, they created a sense of place in their tourist village. The primary objective was to understand the role of indigenous entrepreneurs in preserving tourism villages and identifying the challenges faced. The research applied a qualitative approach with a case study method and was conducted in several locations, including Pampang-Kalimantan, Sade-Lombok, and Kampung Ulos-Sumatera, representing various instances of indigenous entrepreneurs managing tourism villages. The analysis focused on the characteristics of indigenous entrepreneurship and the challenges faced. Furthermore, the data were obtained through interviews and documentation with community leaders, business actors, and key figures providing assistance to indigenous entrepreneurs. The results show that indigenous entrepreneurs play a crucial role in preserving a sense of place in the respective tourism villages. These characteristics influence the physical, social, and shared meanings constituting a sense of place. However, the entrepreneurs face various challenges in the preservation efforts, including issues related to costs, management of traditional spaces for homestays and guest houses, financial support and administration, limited management and tourism-supporting facilities, enhancing storytelling, and sustainable tourism packaging for area marketing.Â